The impact of nepotism on employee organisational attitudes in accommodation enterprises - Topsakal,Yunus (2024)
Abstract This study investigates the impact of nepotism in the hotel industry on affective organisational commitment, identity, cynicism, and trust. These key factors, which are the focus of the study, will be analysed in detail to provide a sector-specific perspective. The research will mainly focus on understanding the sector-specific dynamics of each effect by concentrating on the employees' perceptions of these factors. The results of a survey conducted on 397 employees employed in 5-star hotels in Northern Cyprus found that nepotism exerts an adverse influence on employees' levels of affective organisational commitment, organisational identification, cognitive cynicism, behavioural cynicism, affective cynicism, trust in supervisors, and trust in co-workers. These implications underscore the importance for business managers to address issues related to the perception of nepotism, as doing so can significantly enhance the overall performance of their organisations. This study contributes to the existing literature by filling a knowledge gap and offering valuable insights for academics, researchers, and other stakeholders.